Union Contracts and the Life-Cycle/Permanent-Income Hypothesis - Shea, John (American Economic Review, 1995)
This paper isolates households in the PSID whose heads can be matched to particular long-term union contracts with high confidence. I use published information on these contracts to construct a household-specific measure of expected wage growth. I find that predictable wage movements are significantly correlated with consumption changes, contrary to neoclassical consumption theory. I find that consumption responds more strongly to predictable income declines than to predictable income increases. This asymmetry is inconsistent with liquidity constraints and myopia but is qualitatively consistent with models in which preferences exhibit loss aversion.